A possible way to naturalize the human soul - José Luis Guijarro Morales (Pragmalingüística)
One of the most basic linguistic principles (or parameters, according to some) is used to point to a likely necessary (though, probably, not sufficient) condition of human uniqueness (i.e. being able to speak, communicate complex messages, have religious feelings, indulge in art and humour, and so on) which has been conceptualised either as the fact that we have human souls, in religious contexts, or human minds, in other contexts.